VISUALISASI DATA STOK BARANG PADA PT BECEK GRUP INDONESIA - Mega Pertiwi; Tony; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Skripsi dashboard to monitor incoming and outgoing stock, sales volume, and analyzing the best-selling products of the month at PT Becek Grup Indonesia. The dashboard is well designed to provide accurate and credible information about stock items, so that PT Becek Grup Indonesia can make the right and optimal decisions. The methodology used in this study was interview, observation, and data analysis through the prototyping method. The results of the research show that stocks go in and out and identify a product accurately and provide effective information. In addition, this dashboard has a visualization designed using Power BI so that users can easily use it and can be accessed via mobile devices. Then the visualized data is expected to improve service quality at PT Becek Grup Indonesia and provide significant benefits for warehouse management. Then the data that has been visualized can be used to make it easier for users to find out the details and information they want to know